Optimized fishing through periodically harvested closures - Fraser Januchowski-Hartley (Journal of Applied Ecology, 2019)
1. Periodically harvested closures (PHCs) are a traditional form of fisheries management that improve fishing efficiency during harvests, partly by reducing fish wariness to fishers during closed periods. However, whether PHCs also result in high yields and healthy marine ecosystems is unknown, even as PHCs are being promoted as a culturally appropriate management tool in the Indo-Pacific.2. We integrated field-derived estimates of change in fish wariness into a bioeconomic fisheries model to quantify to what degree PHCs can maximize harvest efficiency, fisheries yield and fish stock biomass.3. Our model indicated that PHCs that had a closure period of one to a few years between a single pulse harvest were able to generate equivalent fisheries yield and stock biomass levels, with greater harvest efficiency than was able to be achieved using permanent closures and other fisheries management tools.4. Fish life-history traits had little impact on the optimality of PHCs in maximizing the triple objective of harvest efficiency, fisheries yield and stock abundance, with overfishing similarly having little effect at anything under extreme levels. Under moderate overfishing, there was a trade-off between PHCs, which maximised harvest efficiency, and no-take permanent closures that maximised yield. However, the former outweighed the latter, and only at extreme levels of overfishing, where stock was reduced to < 18 % of unfished biomass, were permanent closures favoured over PHCs.